Access to markets for smallholder farmers in Alto Molócue and Molumbo, Mozambique: Midline survey report of the INOVAGRO II impact evaluation project - Smart, Jenny; Ghebru, Hosaena; Mogues, Tewodaj (International Food Policy Research Institute, 2019)
This report presents the data from a midline data collection effort as part of the impact evaluation of Phase II of the Innovation for Agribusiness (INOVAGRO II) intervention in northern Mozambique. INOVAGRO II is a development program intended to decrease rural poverty by improving the connectedness of farmers to market systems. The midline data were collected during the intervention phase, in two districts in Zambézia province - Alto Molócue and Molumbo - during the months of late October to December of 2017. The questionnaire focused on agricultural production and market access for all crops, and particularly for the INOVAGRO value chain crops - soybean, pigeon pea, and maize. The purpose of the report is to describe the data, focusing on key variables.